ANALISIS KENYAMANAN THERMAL DAN KENYAMANAN VISUAL PADA RUMAH NELAYAN DI PESISIR PANTAI KELURAHAN LEATO SELATAN - Niniek Pratiwi; Mohammad Imran; Apriyanto; Herawati S. Kupang (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
This study aims to analyze thermal and visual comfort in fishermen's houses on the coast of Leato Selatan Village, Gorontalo City. The research method uses a quantitative approach with direct measurements using digital instruments including infrared thermometers, digital anemometers, digital hygrometers, altimeter barometer thermometer compasses, digital thermocouples, and lux meters. Data was collected from two fishermen's houses as case studies with three measurements taken. The results showed that wood provided better thermal insulation than zinc, while cross ventilation with sea breezes effectively created natural cooling. Houses with optimal orientation and openings were able to meet the natural lighting standard of 200-350 lux, but some interior areas still lacked lighting. The data accuracy rate reached 80% with student comprehension at 85%. This research provides a basis for the development of coastal architectural designs that are responsive to the tropical climate by integrating the local wisdom of the fishing community.